2017
DOI: 10.4174/astr.2017.92.2.55
|View full text |Cite
|
Sign up to set email alerts
|

A novel panel of serum miR-21/miR-155/miR-365 as a potential diagnostic biomarker for breast cancer

Abstract: PurposeInsufficient sensitivity and specificity prevent the use of most existing biomarkers for early detection of breast cancer. Recently, it was reported that serum microRNAs (miRNAs) may be potential biomarkers in many cancer diseases. In this study, we investigated whether serum levels of 5 miRNAs including miR-21, miR-125b, miR-145, miR-155, and miR-365 could discriminate breast cancer patients and healthy controls.MethodsSerum levels of miRNAs were measured by using quantitative real-time polymerase chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 29 publications
5
54
2
1
Order By: Relevance
“…miR-21 has been frequently reported to be aberrantly overexpressed in diverse tumors, including glioblastoma, breast cancer and malignant cholangiocytes (22,23). Recently, miR-21-5p was also reported to be overexpressed in gastric cancer (24).…”
Section: Discussionmentioning
confidence: 99%
“…miR-21 has been frequently reported to be aberrantly overexpressed in diverse tumors, including glioblastoma, breast cancer and malignant cholangiocytes (22,23). Recently, miR-21-5p was also reported to be overexpressed in gastric cancer (24).…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancers, miR10b, miR125b and miR145 are consistently found to be down-regulated and miR21, miR155 are consistently up-regulated [41,42]. It was also reported that miRNAs can still be detected from formalin fixed and paraffin embedded tissue samples, collected blood and serum too.…”
Section: Methods To Detect Mirnas In Breast Cancermentioning
confidence: 97%
“…Furthermore, miR-365-3p has been reported to serve as a therapeutic biomarker for various cancers and tumors such as lung cancer [39,40], colon cancer [28], pancreatic cancer [41], breast cancer [42] and gastric tumorigenesis [43]. Moreover, miR-365-3p inhibited vascular smooth muscle cell proliferation through targeting of CCND1 [44].…”
Section: The Expression Pro Le and Functional Roles Of Bta-mir-365-3pmentioning
confidence: 99%